Diagnostic Test of PIVKA-II as A Tumor Marker for Hepatocellular Carcinoma - Dwi Priyadi Djatmiko; I Putu Adi Santosa; Elvin Richela Lawanto; Bogi Pratomo; Hani Susianti (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Alpha-Fetoprotein (AFP) is a tumor marker that has been widely used for HCC, but there has been no increased AFP in35-45% patients with HCC. Protein induced by vitamin K absence or antagonist II (PIVKA-II) is abnormal prothrombinsecreted in HCC and is expected to be used as a diagnostic marker of HCC. The objective of this study was to compare serumPIVKA-II levels in the patients with HCC, cirrhosis, and healthy control and determine the diagnostic value of PIVKA-II forhepatocellular carcinoma. This was a cross-sectional, analytical observational study to identify the diagnostic value ofPIVKA-II for HCC diagnosis. The diagnosis of 20 cirrhotic patients and 15 patients with HCC was established by using medicalhistory, physical examination, and additional tests according to the diagnosis criteria. A group of 12 individuals with normalliver function was used as healthy control subjects. Serum PIVKA-II levels were analyzed with the immunoassay method. Forthe comparison study, the independent-samples Kruskal Wallis test was used. Also, to determine sensitivity, specificity,positive and negative predictive value (PPV and NPV), ROC curve analysis, and 2x2 contingency table was used. The serumPIVKA-II levels in the patients with HCC were significantly higher than in cirrhotic patients (p=0.000) and healthy control(p=0.000). Sensitivity, specificity, PPV, and NPV of PIVKA-II for diagnosis of HCC in cirrhotic patients at a cut-off value of140.85 mAU/mL were 93.33%, 75%, 73.68%, and 93.75%, respectively (AUC=0.87).PIVKA-II had a high diagnostic value forHCC diagnosis. Diagnostic tests that compare serum PIVKA-II levels in any size of HCC nodules might be needed in thefuture.